Relationship between early musical training and detection of binaural gap based on interaural correlation change - Wang, Mengyuan; Hu, Senlan; Liu, Jinjun; Ai, Mei; Kong, Lingzhi (Frontiers in Neuroscience, 2025)
IntroductionThe auditory fusion of binaural sounds and the perceived auditory image are determined by the similarities of the sounds at the two ears. Sensitivity to the change in interaural correlation, a measure of interaural similarity, is crucial to extract target sound from noisy background. Although musicians have been found to perform better than non-musicians in various types of auditory processing tasks such as frequency discrimination or temporal resolution, the relationship between musical training and the interaural correlation processing remains poorly understood.MethodsHere we embedded a fragment of interaurally uncorrelated noises (interaural correlation = 0) into the interaurally identical marker noises (interaural correlation = 1) and constructed a binaural gap based on the change in interaural correlation (from 1 to 0 then back to 1). The minimum duration of interaurally uncorrelated fragment for detecting the binaural gap (duration threshold) was determined for groups of young adults without musical training and those who started musical training early (before 7 years of age) or late (after 8 years of age).ResultsWhen the binaural noises arrived simultaneously (Experiment 1), we found that the duration threshold was significantly correlated with the onset age of musical training for the early-trained musicians but no such significant correlation was observed for the late-trained musicians. Moreover, the duration thresholds for the early-trained musicians were significantly shorter than those for both the late-trained musicians and non-musicians. When interaural delay was introduced (Experiment 2), this early-musical-training-related enhancement in interaural correlation processing was maintained for binaural noises when the interaural delay was 2 ms, while no enhancement was found when the interaural delay was 4 ms.DiscussionOur findings suggest that sensitivity to dynamic changes in interaural correlation might be influenced by musical training in early childhood, implying a sensitive period when musical training has a significant impact on interaural correlation processing.